TINGKAT KESADARAN PEREMPUAN TERHADAP KONSERVASI AIR DALAM MENDUKUNG PEMBANGUNAN BERKELANJUTAN DI JABODETABEK - Koes Paulina Cantik, Bella; W, Anastasia; Fadilah, Shofwatul; Atika Putri, Hananda; Stephanie, Kezya (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2025)
Water use needs to be balanced with efficient management efforts so that quality and quantity are maintained along with population growth. One of the efforts that can support the maintenance of water quality and quantity is water conservation. Therefore, the role of women as the dominating party in water use and control is important in efforts to improve water conservation. This research uses Regression Analysis with 469 respondents, with the criteria that respondents are women over 16 years old and domiciled in the Jabodetabek area. A descriptive quantitative method is used for this research, by classifying the dependent variables, namely listening intensity, knowledge, so-cialization, implementation, and knowledge distribution. The selected independent variables were age, education, occupation, income, and ethnicity. These variables became the reference in making questionnaire questions to find out the factors that most influence water conserva-tion. The results showed that the knowledge factor possessed by respondents was the main factor influencing the level of awareness in the implementation of water conservation, with a category average value of 4,12. This is supported by the results of the study which show that respondents with a doctoral level of education have a much higher level of awareness than those with a junior high school level of education, with a mean score of 3,36.